Peran Pelindo dalam Lalu Lintas Perdagangan Luar Negeri di Pelabuhan Makassar Pada Masa Pandemi Covid-19 - Zainal, Nur Aliyah; Bachtiar, Farahdiba Rahma; Aisyah, Andi Annur; Rahmadani, Nurul Huda (Review of International Relations, 2024)
World trade traffic is very complex because it involves various actors, crosses various routes, distributes various goods and uses various means of transportation. However, international trade using sea transportation still dominates. Unfortunately, the Covid-19 Pandemic has had a broad impact, including on international trade conducted by Indonesia. For this reason, this research seeks to examine the role of PT Pelabuhan Indonesia IV (Pelindo) in international trade flows, specifically focusing on international trade flows at Soekarno Hatta Port, Makassar during the Covid-19 pandemic. Second, exploring what are Pelindo's obstacles in international trade flows at the Soekarno Hatta Port, especially during the Covid-19 pandemic? This study uses a qualitative approach to examine more deeply the two research focuses. The data used are primary data obtained from interviews and secondary data derived from literature studies. Using the concept of sea transportation and theories regarding the role of government as well as international trade theory, this research finds that PT Pelindo Makassar plays a major role in regulating the flow of container traffic entering and leaving the Port of Makassar. PT Pelindo Makassar, as the only state-owned company assigned by the state, is vital in ensuring that international trade flows can continue even during the Covid-19 pandemic. Meanwhile, during the Covid-19 Pandemic, even though international trade volume was affected by the Large-Scale Social Restrictions (PSBB) policy and often faced delays and quarantine, PT Pelindo Makassar was able to survive because it had an integrated system with other stakeholders. So, do not face such a big obstacle. This data was obtained from direct interview data both by PT Pelindo Makassar itself and partners who use the services of the BUMN.